SURROGACY FROM AN INDIAN PERSPECTIVE (Journal of Forensic Medicine & Toxicology, 2021)
This paper discusses the possibility of curbing the exploitation of surrogates vis-a-vis ensuring the welfare of baby along with prospective parents amid call of a prospective advocacy regarding prohibition of commercial surrogacy in a developing nation like India. Authors also scrupulously determine against depriving joy out of both the parties in commercial surrogate hood contract in case of a legal stricture which prohibits relationship that is anticipated to be mutually beneficial. The paper thrusts to have a relook accounting the wider social, ethical and egalitarian parenthood right issues that may arise out of total legislative ban of commercial surrogacy. A comprehensive analysis of the landmark cases of commercial surrogacy is another highlight of this review.
Keywords: Assisted reproductive techniques; Surrogacy; Womb renting; In-Vitro fertilization; Artificial insemination